Exploring the perceived impact of physical activity on physical and mental health among individuals with long COVID: A qualitative interview inquiry - Zoe Sirotiak; Ann M. Oberhauser; Arie M. Sirotiak; Kate A. Nettleton; Duck-chul Lee; Emily B. K. Thomas; Angelique G. Brellenthin (PLoS ONE, 2026)
Objectives Long COVID presents a significant health burden with limited treatment options. Physical activity (PA) has been suggested for self-management, yet symptom worsening has been reported in similar patient populations. This study aims to identify PA’s perceived impact on physical and mental health in adults with long COVID. Methods Semi-structured interviews were conducted with 34 adults (mean age 52 years, 62% women) based in the United States (U.S.) self-reporting long COVID. PA-related content was analyzed using deductive thematic analysis, assessing worsened and improved health experiences attributed to PA. Results Participants’ perceived health scores were one standard deviation worse than the general U.S. population. Most participants (64.7%) reported worsening long COVID symptoms with PA, while 14.7% noted improvement. Themes for worsened physical health included post-exertional malaise, specific symptom worsening (e.g., fatigue), limited PA abilities, external control perceptions, forced inactivity, and loss of previous PA abilities. Improved health themes involved beliefs in health benefits, symptom improvement, increased energy, accomplishment, enhanced PA abilities, and hope. Discussion PA’s impact on health varied among individuals with long COVID, highlighting the need to tailor PA recommendations to individual needs and limits.